Integration of the High-tech and Low-tech in Distance Teacher Training in China: An insight from the case of Jiangsu Radio and Television University - Xiangyang Zhang (Athabasca University Press, 2007)
This paper reports the result and subsequent exploration of the pilot multi-media in-service teacher training programme with BA degree (non-honour) ( English Language Education) undertaken in the past three years (2001-2004) in China’s distance education. Through the integration of low-tech and high-tech in instructing and delivering courses, many interesting findings have been unexpectedly obtained. Both the trainers (the university lectures) and trainees (in-service school teachers) have experienced a great transformation in their language teaching and learning: a). the trainees (in-service school teachers) have become more independent learners since they raised their educational level; b). the trainers (university lecturers) have learned to adjust their roles in classroom teaching: to be more learner-centred and less teacher-centred; c). acommunicative task-based approach has been satisfactorily adopted and implanted into the process of learning and teaching; d). the trainees have not only upgraded their qualifications but also their teaching methodology. Based on the findings from the case, the authors offer suggestions for the future development of distance teacher training.